2013
DOI: 10.1007/s10803-013-1853-4
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analyses of Expressive Language Development Reveal Two Distinct Language Profiles Among Young Children with Autism Spectrum Disorders

Abstract: Although children with ASD show significant variation in language skills, research on what type(s) of language profiles they demonstrate has been limited. Using growth-curve analyses, we investigated how different groups of young children with ASD show increases in the size of their lexicon, morpho-syntactic production as measured by Brown’s 14 grammatical morphemes, and wh-question complexity, compared to TD children, across six time points. Children with ASD who had higher verbal skills were comparable to TD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
127
2
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(145 citation statements)
references
References 40 publications
(74 reference statements)
6
127
2
3
Order By: Relevance
“…Investigation into lexical and grammatical skills indicated similarities across the semantic categories and early grammatical complexity of toddlers with ASD as compared with late-talking toddlers (Ellis Weismer et al, 2011). Differences in the trajectory of expressive language growth have been observed in high-and low-verbal toddlers with ASD; high-verbal toddlers demonstrated trajectories comparable to toddlers with typical development (Tek, Mesite, Fein, & Naigles, 2014). These studies provide information regarding similarities and differences of the social communication profiles and developmental trajectories of toddlers with ASD in comparison with toddlers with typical development and toddlers with language delays.…”
mentioning
confidence: 94%
“…Investigation into lexical and grammatical skills indicated similarities across the semantic categories and early grammatical complexity of toddlers with ASD as compared with late-talking toddlers (Ellis Weismer et al, 2011). Differences in the trajectory of expressive language growth have been observed in high-and low-verbal toddlers with ASD; high-verbal toddlers demonstrated trajectories comparable to toddlers with typical development (Tek, Mesite, Fein, & Naigles, 2014). These studies provide information regarding similarities and differences of the social communication profiles and developmental trajectories of toddlers with ASD in comparison with toddlers with typical development and toddlers with language delays.…”
mentioning
confidence: 94%
“…However, children with ASD with lower verbal ability typically make slower progress and have flatter language trajectories (Tek, Mesite, Fein, & Naigles, 2013). One study of language growth in children with ASD found several factors (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…As children develop better language skills, they are able to access the pronoun paradigm with greater facility, and the reversals cease. On this account, a higher rate of pronoun reversals in children with ASD may be attributable to their delayed onset of language (Tager-Flusberg et al, 1990; Tek, Mesite, Fein & Naigles, 2014), and/or subtle deficits in their use of specific grammatical forms (Eigsti, Bennetto & Dadlani, 2007; Tager-Flusberg, 2006). Across multiple studies, both TD children and children with ASD have been reported to use more pronoun reversals in imitative contexts (Dale & Crain-Thoreson, 1993; Evans & Demuth, 2012; Roberts, 1989; Tager-Flusberg et al, 2005), suggesting that these pronouns were not yet linguistically productive (i.e., integrated into the grammatical system).…”
mentioning
confidence: 99%